Parameter study on performance of cooling air inlet in indoor environment - Siti Sunarti Bte Sugito (2016)
Designing the heating, ventilating and air-conditioning (HVAC) to use energy more efficiently leads to lower costs of energy and at the same time, to maintain or improve the thermal comfort for occupants. Computational fluid dynamics (CFD) is able to simulate the expected flows in the rooms and buildings. It gives engineers the ability to predict the airflow within a room. The purpose of this study is to obtain an optimal airflow and temperature distribution of a mixing ventilated room. This study uses FLUENT to simulate the ventilation in simple structures and analyses the airflow patterns in the rooms. Many cases were simulated with varying parameters, namely delivered air velocity, position of inlet(s) and outlet(s) in each room as well as the presence of an average build standing occupant. A simple model using rectangular prisms with a heat flux of 140 W/m² represented an occupant. Temperature contours and airflow pattern were attained from the simulations and then analysed to observe the effects that varying parameters have on thermal comfort for an occupant. After the simulation, it was found that in the three-dimensional room, air inlet and outlet placed on the same wall have better thermal comfort. In addition, air inlet velocity of 1 m/s provides better thermal comfort as compared to a relatively high air velocity. This study enhanced the understanding of the interactions of supplied air velocity, position of inlet(s) and outlet(s) and presence of an occupant. The findings of this study can be applied to real-life situations.